ANALISIS PERAMALAN PENJUALAN AIR MINUM DALAM KEMASAN 240ml PADA PT TRIJAYA TIRTA DARMA (GREAT) DENGAN METODE SINGLE MOVING AVARAGE DAN EXPONENTIAL SMOOTHING - Dita Meliana; Suharto Suharto; Putri Suwarni (Industrika : Jurnal Ilmiah Teknik Industri, 2020)
Companies engaged in the field of product sales or distribution services, definitely want success in their activities in the future. This shows that every company always strives to continue to be able to develop in its business field in the future. Forecasting is a method for estimating a value in the future by using past data. Forecasting can also be interpreted as an art and science to predict future events. Researchers conducted a study by taking a location in PT Trijaya Tirta Dharma bottled water company. The author discusses forecasting sales of 240ml bottled water using two methods, namely Single Moving Average and Exponential Smoothing. The author compares the smallest error rate, the forecasting method chosen is Exponential Smoothing. For the Exponential Smoothing method, the results obtained using alpha 0.2 are for February of 195,767, March 197905, April 199,527, May 213,661, June 227,287, July 238,295, August 246,234, September 263,600, October 256,923, November 266,857, December 238,762. Then the forecast is MFE 22466,593, MAD 22466.593, MSE 55522225874, MAPE 2%.